Essential Oil Composition, Antimicrobial Potential, Phytochemical Profile and Toxicity of Essential Oils and Crude Extracts of Sweet Basil Prior and After Flowering - Rangasamy, Oumadevi; Mahomoodally, Mohamad Fawzi; Subratty, Anwar Hussein; Gurib-Fakim, Ameenah (International Journal of Biotechnology for Wellness Industries, 2012)
Essential oils and crude extracts of sweet basil (Ocimum tenuiflorum - OT) which are mostly used to flavor and spice food were prepared and analyzed prior and after flowering by GC and subjected to in vitro antimicrobial and in vivo toxicity evaluation. The essential oil composition was found to vary considerably with respect to harvesting time (prior to flowering stage- eugenol- 17.7%, carvacrol- 27.1% and methyl-eugenol- 52.1%; as compared to flowering (caryophyllene- 9.26% and methyl-eugenol and comparatively smaller percentages of carvacrol and eugenol). Phytochemical screening of the plant samples from either season showed that the whole plants constituted of alkaloids, flavones, saponins, terpenes, sterols, tannins and triterpenes. The essential oils and crude extracts of plant parts of OT (leaves, twigs and/or inflorescence) in both stages showed marked antimicrobial activity against S. aureus and methicillin-resistant S. aureus and with no apparent toxicity in rats. The observed antimicrobial properties and non-toxic nature during both stages of flowering would tend to validate the medicinal properties of OT as a functional food.